THE RESPONSE DIFFERENT APPLE TRANSPLANTS (MALUS DOMESTICA BORKH.) CULTIVARS TO AUTUMN BUDDING DATES AND BALANCED FERTILIZERS IN REGARD OF BUD TAKING AND GROWTH CHARACTERISTICS - NAAMAN, ZAMAN S.; KAKO, SULAIMAN M. (Journal of Duhok University, 2022)
This experiment was conducted during 2021-2022 in the Duhok University nursery, Iraqi Kurdistan region, to study the effects of three different Apple cultivars (Super red, Scarlet and Royal caka), three different budding dates (28th August,18th September and 8th October of 2021) and three levels of balanced fertilizer N20%, P20% and K20 %; (0 g, 2g and 4g. l-1) on the budding successful percentage and some vegetative growth characteristics of apple transplants. The results indicated that the Royal caka cultivar had significant effect on the budding success percentage, transplant(scion) height, transplant (scion) diameter, lateral branches number, leaves number and single leaf area. On the other hand, the date (8th Oct.) give the highest significant effect on budding success, transplant(scion) height, leaves number, and single leaf area. However, the 3rd fertilization concentration (4 g. l-1) had a significant effect on the budding success percentage, transplant (scion) height and transplant (scion) diameter, lateral branches number, leaves number and single leaf area. The triple interaction among (Royal caka cultivar + 3rd budding date (8th Oct.) + 3rd fertilization concentration (4 g. l-1) significantly affected on budding successful percentage and most vegetative growth characteristics